Calcium peroxide (CaO2) granules enclosed in textile materials as H2O2 delivery systems to mitigate Microcystis sp. - Keliri, Eleni; Adamou, Panayiota; Efstathiou, Nektarios; Antoniou, Maria G. (My University, 2022)
The past years, hydrogen peroxide (H2O2) has been introduced as an environmentally friendly method to combat in-situ toxic cyanobacteria blooms because of its selective oxidation and zero waste production. Treatment with H2O2 proved to be efficient for several occasions and blooming events as it selectively suppresses cyanobacteria by inhibiting their photosynthetic activity [1,2]. However, blooms of Microcystissp. that were more persistent required higher H2O2 doses (> 7 mg/L) during treatment, doses that found to cause mobility issues to the zooplankton community of the aquatic ecosystem [3]. Calcium peroxide (CaO2) granules are an alternative to liquid H2O2 due to their slow H2O2 release properties, simulating multiple H2O2 doses [4]. In this study, concentrations of 0.5, 1.0, and 2.0 g/L CaO2 granules were (a) added into a surface water matrix to investigate their H2O2 releasing properties, (b) enclosed in four types of textile materials as delivery systems to evaluate their overall oxidant releasing capacity and (c) enclosed systems A – C were applied on a dense Microcystis sp. bloom to further investigate their suitability to combat cyanobacteria. No difference was observed between the maximum H2O2 concentrations of the direct application of granules and the fabric delivery systems of types A – C, which released up to 12 mg/L H2O2 from 2.0 g/L CaO2 granules. Fabric system type D had the lowest H2O2 releasing capacity (2.0 mg/L of H2O2 from 2.0 g/L CaO2 granules). Treatment experiments showed that granules enclosed in fabrics (GEF) type B of concentration 2 g/L and type C concentrations of 1 g/L and 2g/L were sufficient to reduce the photosynthetic activity of Microcystis species (<1000 RFU), proving that these delivery systems have the potential to become a more environmentally friendly alternative to H2O2. The process minimizes granules availability into the water matrix, and hence eliminate adverse impact on nontargeted species. Moreover, GEF systems promote circular economy by implementing practices that make use of reused and recycled fabrics.
Keywords: oxidation; cyanobacteria; calcium peroxide; granules; fabrics